The impact of OBS burst aggregation on VBR performance - Al-Shargabi, Mohamad Abdulatef; Abid, Abdulwahab (2007)
Video and audio communications like video conference, news, and chat applications are candidates to be the greater portion of internet traffic. Thus, using compressed video and audio traffic seems to be compulsory to reduce the costs of transmission. and storage. Variable Bit Rate (VBR) compressed video and audio traffic have been receiving considerable attention due to their compression algorithms that transmit higher rate during high activity and low rate during less activity. This way of transmission creates a bursty traffic. Thus transporting bursty traffic crosses the network and needs a suitable environment to efficiently allocate network resources. Optical Burst Switching (OBS) is an optical environment that is suitable for bursty traffic. In this paper, we examine the conformity between OBS networks and VBR traffic by developing a simulation model to study the impact of OBS burst aggregation on VBR performance.